Academic Productivity of Equity-Deserving Physician Scholars During COVID-19: A Scoping Review. (20th September 2022) - Soklaridis, Sophie; Black, Georgia; LeBlanc, Constance; MacKinnon, Kinnon R.; Holroyd-Leduc, Jayna; Clement, Fiona; Schrewe, Brett; Ross, Heather J.; Calleja, Sabine; Stergiopoulos, Vicky; Taylor, Valerie H.; Kuper, Ayelet
Abstract : Purpose: The COVID-19 pandemic presented new barriers and exacerbated existing inequities for physician scholars. While COVID-19's impact on academic productivity among women has received attention, the pandemic may have posed additional challenges for scholars from a wider range of equity-deserving groups, including those who hold multiple equity-deserving identities. To examine this concern, the authors conducted a scoping review of the literature through an intersectionality lens. Method: The authors searched peer-reviewed literature published March 1, 2020, to December 16, 2021, in Ovid MEDLINE, Ovid Embase, and PubMed. The authors excluded studies not written in English and/or outside of academic medicine. From included studies, they extracted data regarding descriptions of how COVID-19 impacted academic productivity of equity-deserving physician scholars, analyses on the pandemic's reported impact on productivity of physician scholars from equity-deserving groups, and strategies provided to reduce the impact of the COVID-19 pandemic on academic productivity of physician scholars from equity-deserving groups. Results: Of 11, 587 unique articles, 44 met inclusion criteria, including 15 nonempirical studies and 29 empirical studies (22 bibliometrics studies, 6 surveys, and 1 qualitative study). All included articles focused on the gendered impact of the pandemic on academic productivity. The majority of their recommendations focused on how to alleviate the burden of the pandemic on women, particularly those in the early stages of their career and/or with children, without consideration of scholars who hold multiple and intersecting identities from a wider range of equity-deserving groups. Conclusions: Findings indicate a lack of published literature on the pandemic's impact on physician scholars from equity-deserving groups, including a lack of consideration of physician scholars who experience multiple forms of discrimination. Well-intentioned measures by academic institutions to reduce the impact on scholars may inadvertently risk reproducing and sustaining inequities that equity-deserving scholars faced during the pandemic.